Model Moderasi Beragama Berbasis Pesantren Salaf - Ali Nurdin; Maulidatus Syahrotin Naqqiyah (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2019)
Pondok Pesantren Salaf Al-Anwar, Sarang, Rembang, Central Java, is one of pondok pensantrens based on Nahdlatul Ulama’s moderate (tawassuṭ) understanding, and adheres to the teachings of ahl al-sunnah wa al-jamā‘ah. The purpose of this study is to understand and describe the religious moderation model developed and implemented at Al-Anwar. The results of this descriptive-qualitative study show that the religious moderation model carried out at Al-Anwar is a model of implementing an educational system based on the Salaf curriculum, in which message materials are based on the books of turāth. This model, along with kiai’s strong credibility, becomes an effective media in instilling moderate attitudes for ‘santri’ and the society. The implementation of religious moderation in pesantren can be done through the attitudes and behaviours of santri, which are always guided by the pesantren’s two principles of thought: Firstly, ‘santri’ must have special knowledge as a provision for themselves and general knowledge to face their community. Secondly, ‘santri’ in solving social problems must always refer to the four pillars of the nation.